Multiple Nonfamilial Unilateral Trichoepitheliomas: Report of a Case-Mini Review of the Literature - I. Mandekou-Lefaki; G. Theodosiou; F.-S. Delli; D. Oikonomou; M. Papageorgiou (Hindawi Limited, 2019)
Trichoepitheliomas are benign skin tumors with follicular differentiation that present most commonly as solitary lesions. They can also present as multiple centrofacial papules due to several mutations in the CYLD gene. Multiple unilateral trichoepitheliomas in a linear or dermatomal distribution may rarely be seen. Herein, we report a case of multiple unilateral trichoepitheliomas on the face of a healthy 34-year-old woman of Caucasian origin.